Stiffened Plate Analysis by Considering Follow-up Plates in the Effect of One-Way Axial Load on FPSO Vessels - Ahmad, Rati; Husain, Firman; Alie, Muhammad Zubair Muis (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
Floating Production Storage and Offloading (FPSO) is the portable offshore structure. The material configuration used is the most important aspect in the FPSO structure design criteria. Plates and Stiffened and plates experience local buckling due to the external load when the hull girder collapsed. The objective of the present study is to analyze the stiffened plates taking the attached plate thickness into consideration on the FPSO in term of plate deformation and deflection located of the bottom area under tension and compression stages. In this study the attached plating thickness is varied according to FPSO data and BKI Rule. The stiffened plate elements located at the bottom are modelled by Tee-Bar element. The simply supported condition is applied to the model and the Non-Linier Finite Element Method (NLFEM) is used for the analysis. The result obtained by NLFEM shows that under tension and compression the stiffened plate of model of the thickened plate of the FPSO, the deflection are 1.75 mm and -1.75 mm, respectively. While for model of corrugated plates with BKI minimum intervening plate thickness the deflection are 1.8 mm and -1.8 mm under tension and compression, respectively.